ANALISIS DAYA TARIK AGROWISATA TERHADAP KEPUASAN PENGUNJUNG DI AGROWISATA INPEKMA PT. AGROMAR KELURAHAN KOTA UNENG, KECAMATAN ALOK, KABUPATEN SIKKA - Dewi Derosari, Maria; Anggriani, Yohana; Iawan Saputera Wanda, Taras (Universitas Cokroaminoto Palopo, 2024)
This study aims to identify the elements of agritourism attractiveness to the level of visitor satisfaction. Quantitative research. Activities are carried out Monday to Saturday starting from 08.00-17.00 and carried out at PT Agromar. This activity was carried out for 3 months, starting from September to December 2024. Data obtained directly from the place of internship activities in the form of interviews, observations, documentation, and also by distributing questionnaires are analyzed in order to provide benefits and as one of the considerations in decision making. The results of the research and discussion show that the majority of respondents tend to agree (with an average score in the range of 3.6 to 3.7) on the factors that attract agritourism. This shows that the factors measured, such as the availability of agro-tourism destinations, strategic location, agricultural training services, interesting photo spots, and culinary cafes, play an important role in increasing visitor satisfaction. Each indicator has a consistent average score and shows that this attraction as a whole received a good assessment from the respondents. And based on the predetermined ideal score table, the average score (mean) for each indicator is in the Agree category (mean value between 50-64), which indicates that most respondents feel that the aspects assessed are factors that are quite influential in finding a visitor.